Perceptions of groundwater degradation and mitigation responses in the Haouaria region in Tunisia - Mekki, I.; Ghazouani, Wafa; Closas, Alvar; Molle, Francois (Elsevier, 2017)
Avoiding the negative effects of intensive groundwater resource use is challenging, especially when the interactions and causal pathways between biophysical and socioeconomic processes are complex, and when users, management, and regulatory bodies are spatially dispersed. The plain of Haouaria, in north-eastern Tunisia, has witnessed an important development of groundwater abstraction, fueled by the multiplication of wells tapping the underlying shallow and deep aquifers. As the economic activities linked to such development are threatened by the degradation of groundwater quantity and quality, the aim of this paper is to investigate actors’ perceptions of these processes and to emphasize the undertaken mitigation measures. The study builds on semi-directive surveys with the different groundwater users and archive data in order to understand the technical, institutional and agricultural practices driving groundwater development. The paper starts by investigating the historical context of groundwater development and the progressive degradation of the resource. Then, the paper identifies the main constraints and adaptation strategies of the various users (public and private), before examining the challenges faced by groundwater users. Results show varied patterns of actors' behavior, interest, and perception of the groundwater resource. This analysis show that farmers' lack of collective action, land tenure insecurity, labor shortage, the monopoly of production inputs by suppliers, and the cost of energy for pumping are the main challenges faced by groundwater users. The study finally explores different management and policy options that can lead to a more environmentally and socioeconomically sustainable socio-hydrological system.